2018
DOI: 10.7326/m18-0091
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Single-Sample Confirmatory Testing for Undiagnosed Diabetes

Abstract: National Institute of Diabetes and Digestive and Kidney Diseases and National Heart, Lung, and Blood Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 22 publications
2
37
1
2
Order By: Relevance
“…The Atherosclerosis Risk in Communities (ARIC) study (2018) also showed that the risk of CKD was higher in the DD patients than in the UD patients. The risk factor for each condition was in the sequence: No diabetes < unconfirmed UD < confirmed UD < DD [27]. The findings of the study by Herrington et al and the ARIC study are contradictory to our findings.…”
Section: Ud and The Risk Of Developing Dkdcontrasting
confidence: 99%
“…The Atherosclerosis Risk in Communities (ARIC) study (2018) also showed that the risk of CKD was higher in the DD patients than in the UD patients. The risk factor for each condition was in the sequence: No diabetes < unconfirmed UD < confirmed UD < DD [27]. The findings of the study by Herrington et al and the ARIC study are contradictory to our findings.…”
Section: Ud and The Risk Of Developing Dkdcontrasting
confidence: 99%
“…Unless there is a clear clinical diagnosis (e.g., patient in a hyperglycemic crisis or with classic symptoms of hyperglycemia and a random plasma glucose $200 mg/dL [11.1 mmol/L]), diagnosis requires two abnormal test results from the same sample (32)…”
Section: Confirming the Diagnosismentioning
confidence: 99%
“…The most recent guidelines state that 2 different tests can be obtained from the same blood sample. This new recommendation is based in large part on the results of the long‐term prospective Atherosclerosis Risk in Communities study that examined testing for diabetes using just one sampling of blood . The researchers found that using high values of both a fasting plasma glucose and HgbA1c obtained from the same specimen has a high positive predictive value (88.7%) for the diagnosis of diabetes at a 15 year follow‐up visit.…”
Section: Diagnosis Of Type 2 Diabetesmentioning
confidence: 99%